Correlation between Instability of Blood Glucose Levels and Initial Response of Patients to Wounds to the Degree of Diabetic Foot Ulcer (DFU) - Alfian Mas’ud; Nahman Nahman (Newinera Publisher, 2022)
Instability of blood glucose levels is one of the problems that occur in DFU patients and the patient's initial response to the wound is associated with poor wound healing, amputations, and increased mortality. The research design is an analytic observational study with a cross-sectional approach design. The research subjects were diabetic foot ulcers patients who underwent wound care at the Independent Nursing Practice in Bone Regency. Sampling technique with Total Sampling method. To find out the respondent's blood glucose level, a measurement was carried out using a Portable Glucometer and then an observation was made of the patient's initial response to the wound. DFU degree assessment using Meggitt-Wagner. The tool used to collect data is the respondent's observation data sheet to record all respondent data. After the Spearman correlation test was carried out, the test results were obtained with a value of p = 0.008 and a value of r = 0.472 so that it can be concluded that there is a significant positive correlation between blood sugar levels and the degree of diabetic foot ulcer with moderate correlation strength and based on the results of the Spearman correlation test, the p value is obtained = 0.026 and the value of r = 0.405 so that it can be concluded that there is a significant positive correlation between the patient's initial response to the wound and the degree of diabetic foot ulcer with a weak correlation strength.